2020
DOI: 10.1111/ced.14284
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in exon 1 of the ATP2A2 gene in four members of one Chinese family with Darier disease

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Therefore, ATP2A2 mutation affects Ca 2+ signal and affects the formation of cell adhesion and intercellular connection [1] . Xia Qianqian et al [2] showed that most cases of keratosis of hair follicles (Darier's disease, DD) are caused by mutations in ATP2A2.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ATP2A2 mutation affects Ca 2+ signal and affects the formation of cell adhesion and intercellular connection [1] . Xia Qianqian et al [2] showed that most cases of keratosis of hair follicles (Darier's disease, DD) are caused by mutations in ATP2A2.…”
Section: Introductionmentioning
confidence: 99%